MOZART MUSIC INCREASES THE NUMBER OF GLIAL CELLS COMPARED TO INDONESIA POP AND RELIGIOUS MUSIC - Rahayu, Pipit Sri Estuning; Hermanto, Hermanto; Widjiati, Widjiati (Saintika Medika: Jurnal Ilmu Kesehatan dan Kedokteran Keluarga, 2019)
Music stimulation is an important component for prenatal fetal development. Both pop and religious music are easy to listen and widely accepted in Indonesia. This study was to analyze the effect of Mozart, pop, and religious music exposure during pregnancy to the number of glial cells in the brain of Rattus norvegicus offspring. The samples were divided into three groups based on the exposure for each group, namely Mozart, pop, and religious music, duration of 60 minutes with 65dB intensity, initiated on the 10th day of pregnancy for 9 days in the soundproof chamber. Three brains of the offsprings were dissected and prepared for Hematoxylin-Eosin staining counted on 5 fields of view and 400 magnification strength.Different glial cells number of Rattus norvegicus brain between groups were observed. Mozart music (28,29) showed a highest mean and pop music (18,67)  showed the lowest mean. Significant difference of the number of brain glial cells between Mozart music compared to pop and religious music groups were observed, with p value <0,005.The number of brain glial cells of Rattus norvegicus offsprings in the Mozart group were significantly higher than those in pop and religious groups.